SOCIAL MEDIA STRATEGIES: THE SECRET TO BOOSTING SALES AT COFFEESHOP - Lati Sari Dewi; Adi Anugrah L.H (LP2M Universitas Perjuangan Tasikmalaya, 2025)
This study aims to analyze the influence of social media sharing on increasing sales volume at a coffeeshop. Using a quantitative descriptive method, the study involved 96 respondents selected through an accidental sampling technique. The results show that social media sharing significantly impacts sales volume, with a coefficient of determination of 63.8%. Social media sharing falls into the good category, with the highest score attributed to providing interactive videos, while the lowest score was for organizing online events. Sales volume is also classified as good, with the highest score on reasonable pricing and the lowest on the lack of discounts. It is recommended that the coffeeshop organize online events and offer promotional discounts to attract more customers.